High-entropy alloy oxide catalyst as well as preparation method and application thereof

By using high-entropy alloy oxide catalyst, the bottleneck of the high energy barrier required for N2 dissociation in ammonia synthesis is broken, and the efficient catalytic ammonia synthesis is achieved under mild conditions, which solves the problem of high energy consumption in the traditional ammonia synthesis industry, and significantly improves the reaction rate and catalyst utilization rate.

CN119897125AActive Publication Date: 2025-04-29CHINA ENERGY INVESTMENT CORP LTD +1

Patent Information

Application Number
CN202311404390.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-26
Publication Date
2025-04-29
Estimated Expiration
2043-10-26

AI Technical Summary

Technical Problem

The iron-based catalyst used in the existing ammonia synthesis industry works under high temperature and high pressure, resulting in high energy consumption. In the traditional ammonia synthesis reaction, N2 dissociation requires a high energy barrier, which limits the reaction efficiency.

Method used

Using a high-entropy alloy oxide catalyst, the oxides of high-entropy alloys composed of optional three elements in Fe, Mg, Ti and Mo and Ru and Co elements are broken through the specific alloy element ratio and preparation process to break the N2 dissociation bottleneck in the traditional synthesis ammonia reaction, and catalyzed ammonia synthesis reaction under mild conditions.

Benefits of technology

Under mild conditions (<400°C and 1MPa), the ammonia synthesis reaction rate is significantly improved, energy consumption is reduced, and the utilization rate and thermal stability of the catalyst are improved, and the industrial application prospects are strong.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004516124640000011
    Figure HDA0004516124640000011
  • Figure HDA0004516124640000021
    Figure HDA0004516124640000021
  • Figure HDA0004516124640000022
    Figure HDA0004516124640000022
Patent Text Reader

Abstract

The invention provides a high-entropy alloy oxide catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalyst materials. The catalyst is an oxide of a high-entropy alloy composed of any three elements of Fe, Mg, Ti and Mo, a Ru element and a Co element. The high-entropy alloy oxide catalyst provided by the invention can catalyze an ammonia synthesis reaction under a mild condition; the catalyst has a relatively high ammonia synthesis reaction rate, so that the utilization rate of the high-entropy alloy oxide catalyst is greatly improved, and the catalyst has a relatively strong industrial application prospect; and meanwhile, the catalyst does not have an obvious inactivation phenomenon after long-time operation, and shows extremely high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst materials, and in particular relates to a high entropy alloy oxide catalyst and a preparation method and application thereof. Background Art

[0002] my country is a large agricultural country, and its production and consumption of synthetic ammonia rank first in the world. According to statistics from the Food and Agriculture Organization of the United Nations (FAO), fertilizers contribute more than 40% to food production, and 85% of the world's ammonia is used as fertilizer to meet human agricultural needs. The ammonia synthesis industry not only plays such an important role in agriculture, but is also particularly important in the fields of medicine and military. Researchers have been studying ammonia synthesis reactions for nearly a hundred years and have achieved gratifying results. The study of ammonia synthesis reactions has inspired many catalytic applications, and has also promoted the development of other related disciplines, playing an irreplaceable role in scientific research.

[0003] At present, more than 90% of ammonia is produced by the Haber-Bosch process, and the catalyst used is an iron-based catalyst. The use of iron-based catalysts as ammonia synthesis catalyst requires high temperature and pressure, which consumes a lot of energy. In the past 100 years, the energy consumption of ammonia synthesis has been reduced from about 100GJ / t in the early stage to about 28GJ / t, which is very close to its theoretical value of 20GJ / t. The energy consumption of the ammonia synthesis industry accounts for 1% of the global energy consumption. Therefore, it is imperative to solve the problem of high energy consumption in the ammonia synthesis industry. Summary of the invention

[0004] In order to solve the above problems existing in the prior art, the present invention provides a high entropy alloy oxide catalyst and its preparation method and application. The high entropy alloy oxide catalyst in the present invention can catalyze ammonia synthesis reaction under mild conditions, while improving the reaction performance of the ammonia synthesis catalyst and significantly reducing the energy consumption during the reaction process.

[0005] An object of the present invention is to provide a high entropy alloy oxide catalyst.

[0006] In some embodiments, the catalyst is an oxide of a high entropy alloy composed of any three elements of Fe, Mg, Ti and Mo and Ru and Co. For example, the elements of the high entropy alloy oxide catalyst are Ru, Co, Fe, Mg, and Mo; or the elements of the high entropy alloy oxide catalyst are Ru, Co, Fe, Ti, and Mo; or the elements of the high entropy alloy oxide catalyst are Ru, Co, Fe, Mg, and Ti; or the elements of the high entropy alloy oxide catalyst are Ru, Co, Mg, Ti, and Mo.

[0007] In some preferred embodiments, the elements of the high entropy alloy oxide catalyst are Ru, Co, Fe, Ti, and Mo; in some preferred embodiments, the molar percentages of the Ru element, the Co element, the Fe element, the Ti element, and the Mo element are (5-35):(5-35):(5-35):(5-35):(5-35); in some more preferred embodiments, the molar percentages of the Ru element, the Co element, the Fe element, the Ti element, and the Mo element are (5-20):(5-20):(20-35):(5-20):(5-20); in some most preferred embodiments, the molar percentages of the Ru element, the Co element, the Fe element, the Ti element, and the Mo element are 5:20:35:20:20.

[0008] Another object of the present invention is to provide a method for preparing the high entropy alloy oxide catalyst.

[0009] In some embodiments, the preparation method comprises the following steps:

[0010] 1) mixing any three powders selected from Fe element powder, Mg element powder, Ti element powder and Mo element powder, Ru element powder and Co element powder to obtain a mixture;

[0011] 2) heating and melting the mixture in an inert atmosphere to obtain a high entropy alloy block;

[0012] 3) grinding the high entropy alloy block in an inert atmosphere to obtain a high entropy alloy powder;

[0013] 4) calcining the high entropy alloy powder in air to obtain a high entropy alloy oxide catalyst.

[0014] In some embodiments, in step 1), the purity of any three of the Fe element powder, the Mg element powder, the Ti element powder and the Mo element powder, as well as the Ru element powder and the Co element powder are all higher than 99%, and the particle size is 100-500 mesh.

[0015] In some embodiments, in step 2), the inert gas is argon, and in some preferred embodiments, the purity of the argon is 99%; the heating and melting treatment includes: a heating temperature of 1000-3000°C and a heating time of 10-60 min; in some preferred embodiments, a heating temperature of 1500-2500°C and a heating time of 20-40 min; in some more preferred embodiments, a heating temperature of 2000°C and a heating time of 30 min.

[0016] In some embodiments, the heated melt-casting is performed in a Joule heater.

[0017] In some embodiments, in step 3), the inert gas is argon, and in some preferred embodiments, the purity of the argon is 99%; the grinding treatment is ball milling, and the ball milling jar used is one or more of a vacuum stainless steel jar, a cemented carbide jar and an agate jar; the ball is one or more of a stainless steel ball, a cemented carbide ball and a zirconia ball; the ball milling medium is one or more of anhydrous ethanol, polyvinyl alcohol, stearic acid and polymethyl methacrylate.

[0018] In some embodiments, the ball milling conditions include: a ball milling speed of 200-600 rpm, a ball-to-material ratio of 2:1-20:1, and a ball milling time of 10-100 h; in some preferred embodiments, the ball milling speed is 300-500 rpm, a ball-to-material ratio of 4:1-16:1, and a ball milling time of 20-80 h; in some more preferred embodiments, the ball milling speed is 400 rpm, the ball-to-material ratio is 10:1, and the ball milling time is 30-50 h.

[0019] In some embodiments, in step 4), the calcination is carried out in a muffle furnace; the calcination treatment includes: a calcination temperature of 100-800°C, a calcination time of 10-30h, and a heating rate of 5-20°C / min; in some preferred embodiments, the calcination temperature is 200-600°C, the calcination time is 10-20h, and the heating rate is 10-15°C / min; in some more preferred embodiments, the calcination temperature is 500°C, the calcination time is 12h, and the heating rate is 10°C / min.

[0020] The last object of the present invention is to provide the use of the high entropy alloy oxide catalyst described above or the high entropy alloy oxide catalyst prepared by any of the preparation methods described above in an ammonia synthesis reaction.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] (1) The present invention proposes for the first time the application of high entropy alloy oxide catalysts in ammonia synthesis. The five element atoms of the catalyst are orderly arranged and combined with each other to form an electronic structure different from the original elements, which can break the restrictive relationship, that is, it can break the bottleneck of high energy barrier required for N2 dissociation in the traditional ammonia synthesis reaction process. Specifically, in the process of ammonia synthesis, the catalyst makes N2 (N≡N bond) no longer dissociate directly, but hydrogenates to generate N2H2, and then gradually hydrogenates to release NH3, thus breaking the bottleneck of high energy barrier required for N2 dissociation in the traditional ammonia synthesis reaction process, and finally realizing the catalytic ammonia synthesis reaction under mild conditions (<400℃ and 1MPa); and it has a high ammonia synthesis reaction rate, which greatly improves the utilization rate of high entropy alloy oxide catalysts and has strong industrial application prospects.

[0023] (2) The high entropy alloy oxide catalyst prepared by the present invention using five metals has an excellent electronic structure and the synergistic catalysis of multiple elements enables it to exhibit good catalytic activity.

[0024] (3) The high entropy alloy oxide catalyst in the present invention has higher atomic dispersion and high utilization rate compared with traditional iron-based catalysts due to the mutual isolation of multiple metals. It has good thermal stability for ammonia synthesis under mild conditions, which is conducive to industrial production and provides a new solution for energy saving and consumption reduction in ammonia synthesis reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The ammonia synthesis reaction rate results of the high entropy alloy oxide catalyst prepared in Examples 1-7 of the present invention at a temperature of 380° C. and a pressure of 1 MPa;

[0026] Figure 2 The ammonia synthesis reaction rate results of the high entropy alloy oxide catalyst prepared in Comparative Examples 1-8 of the present invention at a temperature of 380° C. and a pressure of 1 MPa;

[0027] Figure 3 The figure shows the rate stability result when the RuCoFeMoTi high entropy alloy oxide catalyst prepared in Example 3 of the present invention is used for ammonia synthesis reaction. DETAILED DESCRIPTION

[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used are all available from commercial channels unless otherwise specified.

[0030] Example 1

[0031] The elements of the high entropy alloy oxide catalyst are Ru, Co, Fe, Mg and Ti.

[0032] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0033] 1) preparing alloy powders of Ru, Co, Fe, Mg and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:20:35:20:20, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0034] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0035] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoFeMgTi high entropy alloy powder;

[0036] 4) placing the fully alloyed RuCoFeMgTi high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeMgTi high entropy alloy oxide catalyst.

[0037] Example 2

[0038] The elements of the high entropy alloy oxide catalyst are Ru, Co, Fe, Mg and Mo.

[0039] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0040] 1) preparing alloy powders of Ru, Co, Fe, Mg and Mo with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:20:35:20:20, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0041] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0042] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoFeMgMo high entropy alloy powder;

[0043] 4) placing the fully alloyed RuCoFeMgMo high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeMgMo high entropy alloy oxide catalyst.

[0044] Example 3

[0045] The elements of the high entropy alloy oxide catalyst are Ru element, Co element, Fe element, Mo element, and Ti element.

[0046] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0047] 1) preparing alloy powders of Ru, Co, Fe, Mo and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:20:35:20:20, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0048] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0049] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoFeMoTi high entropy alloy powder;

[0050] 4) placing the fully alloyed RuCoFeMoTi high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeMoTi high entropy alloy oxide catalyst.

[0051] Example 4

[0052] The elements of the high entropy alloy oxide catalyst are Ru, Co, Mo, Mg and Ti.

[0053] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0054] 1) preparing alloy powders of Ru, Co, Mo, Mg and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:20:35:20:20, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0055] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0056] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoMoMgTi high entropy alloy powder;

[0057] 4) placing the fully alloyed RuCoMoMgTi high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoMoMgTi high entropy alloy oxide catalyst.

[0058] Example 5

[0059] The elements of the high entropy alloy oxide catalyst are Ru element, Co element, Fe element, Mo element and Ti element.

[0060] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0061] 1) preparing alloy powders of Ru, Co, Fe, Mo and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 1:4:45:25:25, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0062] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0063] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoFeMoTi high entropy alloy powder;

[0064] 4) placing the fully alloyed RuCoFeMoTi high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeMoTi high entropy alloy oxide catalyst.

[0065] Example 6

[0066] The elements of the high entropy alloy oxide catalyst are Ru element, Co element, Fe element, Mo element and Ti element.

[0067] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0068] 1) preparing alloy powders of Ru, Co, Fe, Mo and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:60:15:15, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0069] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0070] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 300 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoFeMoTi high entropy alloy powder;

[0071] 4) placing the fully alloyed RuCoFeMoTi high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeMoTi high entropy alloy oxide catalyst.

[0072] Example 7

[0073] The elements of the high entropy alloy oxide catalyst are Ru element, Co element, Fe element, Mo element, and Ti element.

[0074] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0075] 1) preparing alloy powders of Ru, Co, Fe, Mo and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:80:5:5, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0076] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0077] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 300 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoFeMoTi high entropy alloy powder;

[0078] 4) placing the fully alloyed RuCoFeMoTi high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeMoTi high entropy alloy oxide catalyst.

[0079] Example 8

[0080] The elements of the high entropy alloy oxide catalyst are Ru element, Co element, Fe element, Mo element, and Ti element.

[0081] The preparation method of the high entropy alloy oxide catalyst comprises the following steps:

[0082] 1) preparing alloy powders of Ru, Co, Fe, Mo and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:20:35:20:20, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0083] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a muffle furnace, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0084] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (60-80 mesh) for classification to obtain a fully alloyed RuCoFeMoTi high entropy alloy powder;

[0085] 4) placing the fully alloyed RuCoFeMoTi high entropy alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeMoTi high entropy alloy oxide catalyst.

[0086] Comparative Example 1

[0087] 1) preparing an alloy powder with a purity higher than 99% and a particle size of 300 meshes of Ru and Co in a molar percentage of 50:50, and uniformly mixing the alloy powder in a mixer to obtain an unalloyed mechanical mixed powder;

[0088] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0089] 3) The high entropy alloy block obtained in step 2) is crushed and loaded into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%. The ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCo alloy catalyst.

[0090] Comparative Example 2

[0091] 1) preparing alloy powders of Ru, Co and Fe with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:90, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0092] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0093] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoFe alloy powder;

[0094] 4) placing the completely alloyed RuCoFe alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFe alloy catalyst.

[0095] Comparative Example 3

[0096] 1) preparing alloy powders of Ru, Co and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:90, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0097] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0098] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoTi alloy powder;

[0099] 4) placing the completely alloyed RuCoTi alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoTi alloy catalyst.

[0100] Comparative Example 4

[0101] 1) preparing alloy powders of Ru, Co and Mo with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:90, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0102] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0103] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved (100-120 mesh) for classification to obtain a fully alloyed RuCoMo alloy powder;

[0104] 4) placing the completely alloyed RuCoMo alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoMo alloy catalyst.

[0105] Comparative Example 5

[0106] 1) preparing alloy powders of Ru, Co, Fe and Ti with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:45:45, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0107] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0108] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved and classified (100-120 meshes) to obtain a fully alloyed RuCoFeTi alloy powder;

[0109] 4) placing the completely alloyed RuCoFeTi alloy powder obtained in step 3) in a muffle furnace, heating it to 500° C. at a heating rate of 10° C. / min, and calcining it for 12 h to obtain a RuCoFeTi alloy catalyst.

[0110] Comparative Example 6

[0111] 1) preparing alloy powders of Ru, Co, Fe and Mo with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:45:45, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0112] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0113] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved and classified (100-120 meshes) to obtain a fully alloyed RuCoFeMo alloy powder;

[0114] 4) The completely alloyed RuCoFeMo alloy powder obtained in step 3) is placed in a muffle furnace, heated to 500° C. at a heating rate of 10° C. / min, and calcined for 12 h to obtain a RuCoFeMo alloy catalyst.

[0115] Comparative Example 7

[0116] 1) preparing alloy powders of Ru, Co, Ti and Mo with a purity higher than 99% and a particle size of 300 meshes according to a molar percentage of alloy elements of 5:5:45:45, and uniformly mixing the alloy powders in a mixer to obtain unalloyed mechanical mixed powders;

[0117] 2) placing the unalloyed mechanically mixed powder obtained in step 1) in a Joule heater, introducing argon gas with a purity of 99%, maintaining an inert gas atmosphere, and melting and casting at 2000° C. for 30 minutes to obtain a high entropy alloy block;

[0118] 3) crushing the high entropy alloy block obtained in step 2) and loading it into a ball mill at a ball-to-material ratio of 10:1 under an argon atmosphere with a purity of 99%, wherein the ball mill is a vacuum stainless steel tank, the balls used are stainless steel balls, the ball milling medium is anhydrous ethanol, the ball milling process is a speed of 400 rpm, and the ball milling time is 36 hours. After the ball milling is completed, the prepared powder is taken out, dried in a vacuum drying oven at 80° C. for 1 hour, and then sieved and classified (100-120 meshes) to obtain a fully alloyed RuCoTiMo alloy powder;

[0119] 4) The completely alloyed RuCoTiMo alloy powder obtained in step 3) is placed in a muffle furnace, heated to 500° C. at a heating rate of 10° C. / min, and calcined for 12 h to obtain a RuCoTiMo alloy catalyst.

[0120] Catalyst performance test

[0121] 0.15 g of each catalyst prepared in Examples 1-8 and Comparative Examples 1-7 was taken respectively, and the ammonia synthesis rate was measured in a continuous flow micro fixed bed reactor at a mass space velocity of 60000 mL / (g·h). The change of NH3 concentration in the tail gas was measured by ion chromatography (Thermo Scientific, DIONEX, ICS 600). The reaction gas composition was: 75% H2+25% N2 mixed gas.

[0122] The ammonia synthesis reaction rates of the catalysts prepared in Examples 1-8 and Comparative Examples 1-7 were measured at a temperature of 380°C and a pressure of 1 MPa. The test conditions were the same. The test results are shown in Figure 1 and Figure 2 .

[0123] from Figure 1 It can be seen that the activities of the high entropy alloy oxide catalysts prepared in Examples 1-4 are not much different, among which the high entropy alloy oxide catalyst prepared in Example 3 has the highest activity, reaching 31.1 mmol NH3 / (g cat . h), the results show that the RuCoFeMoTi high entropy alloy oxide catalyst with a molar percentage of alloying elements of 5:20:35:20:20 has the highest activity. Compared with Example 3, the proportions of some alloying elements in Examples 5, 6 and 7 are not within the scope of the present invention, because their lower contents of Ru and Co elements lead to lower activities than the catalyst in Example 3. The results show that the alloy ratio has a certain influence on the activity. The difference between Example 8 and Example 3 is that Joule heating is not used. It is found that the activity of the high entropy alloy oxide catalyst prepared in Example 3 is much higher than that of the high entropy alloy oxide catalyst prepared in Example 8. This is because Joule heating can quickly increase and decrease the temperature, which is beneficial to the uniformity of the metal powder forming the alloy and is beneficial to improving its catalytic activity.

[0124] from Figure 2 It can be seen that in Comparative Examples 1-7, with the increase in the amount of alloy metal elements, the activity of the high entropy alloy oxide catalyst shows an upward trend. The results show that the excellent electronic properties of the prepared high entropy alloy oxide catalyst and the synergistic effect of multiple elements are conducive to the synthesis of ammonia reaction; among them, the catalytic activity of the prepared five-element high entropy alloy oxide catalyst is the highest.

[0125] The RuCoFeMoTi high entropy alloy oxide catalyst prepared in Example 3 was used for the synthesis of ammonia at a temperature of 380°C and a pressure of 1 MPa to study the effect of reaction time on the catalyst activity. The results are shown in FIG. Figure 3 .

[0126] from Figure 3 It can be seen that the RuCoFeMoTi high entropy alloy oxide catalyst continued to operate for 100 hours, and the ammonia synthesis performance did not decrease. The results show that the RuCoFeMoTi high entropy alloy oxide catalyst prepared by the present invention has good stability.

[0127] The above embodiments are only specific implementation methods of the present invention, which are used to illustrate the technical solutions of the present invention rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the aforementioned embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the aforementioned embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the protection scope of the present invention.

Claims

1. A high entropy alloy oxide catalyst, characterized in that: The catalyst is an oxide of a high entropy alloy composed of any three elements selected from Fe, Mg, Ti and Mo, Ru and Co.

2. The high entropy alloy oxide catalyst according to claim 1, characterized in that The elements of the high entropy alloy oxide catalyst are Ru, Co, Fe, Ti, and Mo. Preferably, the molar percentages of the Ru element, the Co element, the Fe element, the Ti element, and the Mo element are (5-35):(5-35):(5-35):(5-35):(5-35); more preferably, the molar percentages of the Ru element, the Co element, the Fe element, the Ti element, and the Mo element are (5-20):(5-20):(20-35):(5-20):(5-20).

3. The method for preparing the high entropy alloy oxide catalyst according to claim 1 or 2, characterized in that: The steps include: 1) mixing any three powders selected from Fe element powder, Mg element powder, Ti element powder and Mo element powder, Ru element powder and Co element powder to obtain a mixture; 2) heating and melting the mixture in an inert atmosphere to obtain a high entropy alloy block; 3) grinding the high entropy alloy block in an inert atmosphere to obtain a high entropy alloy powder; 4) calcining the high entropy alloy powder in air to obtain a high entropy alloy oxide catalyst.

4. The method for preparing a high entropy alloy oxide catalyst according to claim 3, characterized in that: In step 1), the purity of any three powders selected from the Fe element powder, the Mg element powder, the Ti element powder and the Mo element powder, as well as the Ru element powder and the Co element powder are all higher than 99%, and the particle sizes are all 100-500 meshes.

5. The method for preparing a high entropy alloy oxide catalyst according to claim 3, characterized in that: In step 2), the inert gas is argon, preferably, the purity of the argon is 99%; the heating and casting treatment includes: a heating temperature of 1000-3000°C, and a heating time of 10-60min; preferably, the heating temperature is 1500-2500°C, and the heating time is 20-40min; more preferably, the heating temperature is 2000°C, and the heating time is 30min.

6. The method for preparing a high entropy alloy oxide catalyst according to claim 5, characterized in that: The heating and melting is carried out in a Joule heater.

7. The method for preparing a high entropy alloy oxide catalyst according to claim 3, characterized in that: In step 3), the inert gas is argon, preferably, the purity of the argon is 99%; the grinding treatment is ball milling, and the ball milling jar used is one or more of a vacuum stainless steel jar, a cemented carbide jar and an agate jar; the balls are one or more of stainless steel balls, cemented carbide balls and zirconium oxide balls; the ball milling medium is one or more of anhydrous ethanol, polyvinyl alcohol, stearic acid and polymethyl methacrylate.

8. The method for preparing a high entropy alloy oxide catalyst according to claim 7, characterized in that: The ball milling conditions include: a ball milling speed of 200-600 rpm, a ball-to-material ratio of 2:1-20:1, and a ball milling time of 10-100 h; preferably, the ball milling speed is 300-500 rpm, the ball-to-material ratio is 4:1-16:1, and the ball milling time is 20-80 h; more preferably, the ball milling speed is 400 rpm, the ball-to-material ratio is 10:1, and the ball milling time is 30-50 h.

9. The method for preparing a high entropy alloy oxide catalyst according to claim 3, characterized in that: In step 4), the calcination is carried out in a muffle furnace; the calcination treatment includes: a calcination temperature of 100-800°C, a calcination time of 10-30h, and a heating rate of 5-20°C / min; preferably, the calcination temperature is 200-600°C, the calcination time is 10-20h, and the heating rate is 10-15°C / min; more preferably, the calcination temperature is 500°C, the calcination time is 12h, and the heating rate is 10°C / min.

10. Use of the high entropy alloy oxide catalyst according to claim 1 or 2 or the high entropy alloy oxide catalyst prepared by the preparation method according to any one of claims 3 to 9 in an ammonia synthesis reaction.

Citation Information

Patent Citations

  • High-entropy oxides for thermal barrier coating (TBC) top coats

    CN112839915A

  • Bifunctional catalyst, preparation method thereof and metal-air battery

    CN113782755A

  • High-entropy alloy active catalytic material and preparation method thereof

    CN114799193A

  • Axial flow reactor based on an fe-cr-al alloy

    WO2013135666A1

Cited By

  • Porous-structure high-entropy alloy oxygen evolution catalyst and preparation method thereof

    CN122189693A